The demand revolution how consumers are redefining sustainability and transforming the future of business - Gathen, Andreas von der; Eckert, Nicolai Broby; Kastbjerg, Caroline (Ascent Audio, 2025)
Sustainability is rocking the business world as profoundly as any global trend of the past, from electrification to digitalization. But unlike previous revolutions, this one is being driven by consumers, for whom environmentally sound practices matter as much as price, quality, and brand. In The Demand Revolution, Andreas von der Gathen, Nicolai Broby Eckert, and Caroline Kastbjerg offer a strategic framework for winning these consumers--and taking advantage of the vast commercial opportunity presented by sustainability as the first demand-driven, transformative megatrend. The first movers in the Demand Revolution will be able to create enduring competitive advantages and high entry barriers built around redesigned business model ecosystems and customer loyalty, the authors explain, but this will require a critical adjustment in thinking and approach. Companies, first of all, have to catch up with consumers, who see themselves on a demand curve far beyond what companies currently perceive. Business leaders must shift their focus from the cost of sustainability to its potential for generating growth and long-term profits. The Demand Revolution shows business leaders how to look beyond easy fixes and incremental outcomes and instead pursue high-risk, high-reward moves geared toward the source of exponential growth: the world's consumers.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed April 9, 2025)
Keywords: Sustainable development; Consumption (Economics) -- Environmental aspects; Value; Développement durable; Société de consommation; Aspect de l'environnement; Valeur; sustainable development; value (economic concept); Business Ethics; Leadership; BUSINESS & ECONOMICS; Sustainable Development; Development; Audiobooks; Livres audio